1986
DOI: 10.1021/ja00275a012
|View full text |Cite
|
Sign up to set email alerts
|

Angular preferences of intermolecular forces around halogen centers: preferred directions of approach of electrophiles and nucleophiles around carbon-halogen bond

Abstract: During our studies of Se-Se interactions in selenides, it was observed that halogen atoms X of C-X bonds were engaged in both a "head-on" and a "side-on" fashion to Se atoms. To understand such interactions, we have analyzed the crystallographic environment around halogen centers and find that, in general, "electrophiles" tend to approach halogens of C-X (X = Cl, Br, I) at an angle of ~100°and nucleophiles at ~165°and that C-X-X-C type interactions fall into two groups, one forming an "electrophile-nucleophile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
345
1
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 515 publications
(369 citation statements)
references
References 0 publications
20
345
1
1
Order By: Relevance
“…For this reason, the correct description and understanding of noncovalent interactions between molecules is essential for being successful in this field of research. In general, strong and highly directional interactions, such as hydrogen bonding and σ-hole bonding [7][8][9][10][11][12][13][14][15][16][17], and less directional forces like ion pairing are used for this purpose.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, the correct description and understanding of noncovalent interactions between molecules is essential for being successful in this field of research. In general, strong and highly directional interactions, such as hydrogen bonding and σ-hole bonding [7][8][9][10][11][12][13][14][15][16][17], and less directional forces like ion pairing are used for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…electron acceptor) has been explored by Mani and Arunan [41]. They demonstrated that the carbon atom in fact could act as an electrophilic center which can non-covalently bond with electron-rich entities leading to noncovalent carbon bonding, following a nomenclature analogous to other σ-hole interactions [7][8][9][10][11][12][13][14][15][16][17]. The theoretical predictions were confirmed experimentally by Guru Row's group [42], thus validating the existence of this type of bonding by means of X-ray charge density analysis.…”
Section: Introductionmentioning
confidence: 99%
“…For bond-length data, see: Allen et al (1987). For ClÁ Á ÁN halogen bonds, see : Chu, et al (2001); Lommerse et al (1996); Ramasubbu et al (1986). Table 1 Hydrogen-bond geometry (Å , ).…”
Section: Related Literaturementioning
confidence: 99%
“…In the crystal structure of the title compound, there are a weak intermolecular hydrogen bond of one phenyl hydrogen atom towards the nitrile N atom (C8-H8···N4, Table 1) and a nitrogen-chlorine donor-acceptor interaction (Chu, et al, 2001;Lommerse et al, 1996;Ramasubbu, et al, 1986) between the pyrimidinyl N atom and one of the chlorine atoms.…”
Section: Crystal Datamentioning
confidence: 99%
“…The presence of only one non-chlorine donor atom in anhydrous chlorophenolate salts, and that in a some- what sterically hindered position, almost ensures that there must be cation-organochlorine contacts involving these very large metal cations [5]; there are 3.26-Ä K-Cl contacts in the monohydrated potassium salts of the 2-chloro-4-nitrophenolate ion [6] and of the herbicide 2,4-D [7], despite the presence of many more (four) oxygen donor atoms per metal ion. A recent crystallographic database search found eight other structures involving K + -organochlorine contacts of 3.26 Ä and up [8].…”
Section: Introductionmentioning
confidence: 99%